Effect of CNC application parameters on wooden surface quality - Koc, Kücük Hüseyin; Erdinler, Emine Seda; Hazir, Ender; Öztürk, Emel (Measurement : journal of the International Measurement Confederation, 2017)
[Display omitted] •The effects of CNC processing parameters on the surface quality in wood materials were determined.•Laser based robotic system was used for the measurements of the surfaces.•Surface roughness values were affected by the variations of the material subjects. Objective of this study is to determine the parameters such as spindle speed, feed rate and wood material on surface quality. Medium density fiberboard (MDF), Beech (Fagus orientalis L.) and Ayous (Triplochiton scleroxylon) were selected for the study. Wood specimens were prepared using different values of spindle speed and feed rate. Surface roughness (Ra) values of specimens were measured by employing stylus type of equipment and laser based robotic measurement system. Laser based robotic measurements were obtained by Matlab software. The objective of the techniques were to (1) determine the significant parameters on wood surface quality (2) analyze the main and interaction effects in the CNC cutting process (3) compare the data from the robotic system with the stylus type of equipment. As the result of this study, spindle speed of 18,000rpm and feed rate of 2m/min resulted with minimum surface roughness values of MDF, Ayous and Beech wood for laser and stylus techniques.